2017
DOI: 10.3892/br.2017.854
|View full text |Cite
|
Sign up to set email alerts
|

ADAM33 gene polymorphisms identified to be associated with asthma in a Chinese Li population

Abstract: Abstract. A disintegrin and metalloprotease 33 (ADAM33)is an asthma susceptibility gene that has been proven to be present in certain human populations. The Li population is a minority ethnic group, most of whom maintain a distinctive lifestyle on Hainan Island in southern China. To the best of our knowledge, no previous study has established whether ADAM33 polymorphisms are associated with asthma in the Li population. Therefore, the ADAM33 polymorphisms in a Li population were investigated in the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
6
0
4
Order By: Relevance
“…However, a strong LD among these SNPs was not observed, contrary to the findings in our population. Another recent study on a Chinese Li23 population reported the significant association of rs2280089, and the non-significant association of rs2280091 with susceptibility to asthma. The same study also predicted a low LD between the SNP variants in the Li population.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, a strong LD among these SNPs was not observed, contrary to the findings in our population. Another recent study on a Chinese Li23 population reported the significant association of rs2280089, and the non-significant association of rs2280091 with susceptibility to asthma. The same study also predicted a low LD between the SNP variants in the Li population.…”
Section: Discussionmentioning
confidence: 94%
“…The allele and genotype frequencies of these variants were also found to be non-significant after stratification based on age, gender, family history of asthma in asthmatics, and urban/rural/semi-urban population. Despite the reported significant associations of these SNPs with asthma in multiple populations, no significant association has been identified in sub-ethnic populations of the same origin 8,14,16,23. A recent study based on 2 cities of Pakistan (Islamabad and Lahore) reported a protective role of rs2280091 against asthma in a Pakistani population 24.…”
Section: Discussionmentioning
confidence: 99%
“…ADAM33 is expressed in the smooth muscle, myofibroblasts, and fibroblasts of asthmatic airways, thus the function of this protein might be involved in the airway remodeling [ 35 ]. Various lines of evidence from previous human and animal studies have indicated that the expression level of ADAM33 was upregulated during acute or chronic lung inflammation [ 36 ]. Even though the existence of this functional link between ADAM33 and allergic airway inflammation, its role in the pathophysiology of AR is still to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…ADAM33 is expressed in the smooth muscle, myo broblasts, and broblasts of asthmatic airways, thus the function of this protein might be involved in the airway remodeling (35). Various lines of evidence from previous human and animal studies have indicated that the expression level of ADAM33 was upregulated during acute or chronic lung in ammation (36). Even though the existence of this functional link between ADAM33 and allergic airway in ammation, its role in the pathophysiology of AR is still to be clari ed.…”
Section: Discussionmentioning
confidence: 99%